The Reject Green Kale Substitution (Ipomoea Aquatica) Fermented Yeast in Commercial Feed on Performance and Carcass Quality of Super Native Chicken - Alberth Nugrahadi Ndun; Franky M. S. Telupere; Ni Gusti Ayu Mulyantini (TERNAK TROPIKA Journal of Tropical Animal Production, 2020)
The purpose of this study was to determine the reject green kale effect of substitution fermented yeast in commercial feed on the performance and carcass quality of super native chicken. The design of this study is a completely randomized design (CRD) factorial pattern 2 x 4. The first factor is gender, the second factor is 4 treatment of feed. Each treatment consisted of 4 replications, and each test consisted of 4 chickens. The treatment in question is: R0 = (100%) basal ration without the reject green kale substitution (Control), R1 = 95% basal ration + with the reject green kale substitution fermented yeast 5%, R2 = 90% basal ration + with the reject green kale substitution fermented yeast 10%, R3 = 85% basal ration + with the reject green kale substitution fermented yeast 15%. Conclusion the reject green kale substitution fermented yeast in commercial feed can improve the performance and carcass quality of super native chicken. The best performance results were obtained from the value of feed consumption in male R3 treatment at 455.6 grams/head/week, body weight gain/week in male R3 treatment at 295.5 grams/head/week, feed conversion in male R2 treatment at 1,538, and carcass percentage at male R3 treatment by 62.6%. While the best results of carcass quality obtained from the value of the water holding capacity is the treatment of male R1 by 53.83%, cooking losses in the treatment of R3 female by 12.63%, the potential hydrogen of the male R2 treatment by 5.07%, and tenderness which is at the highest favorite level in the treatment of treatment. Male R3 is 3.53%.